2003
DOI: 10.1002/cncr.11652
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum MUC5AC mucin in patients with cholangiocarcinoma

Abstract: Tissue inhibitor of metalloproteinase‐2 (TIMP‐2) is an endogenous inhibitor of matrix metalloproteinases (MMPs). This multifunctional protein regulates activities of MMPs and possesses growth promoting effect in cell culture, anti‐tumoral, anti‐apoptotic and anti‐angiogenic effects in animal model systems in vivo. It has been shown that this gene is downregulated in cervical carcinomas. The mechanism of inhibition of TIMP‐2 expression remains obscure. We have examined whether aberrant DNA methylation of the 5′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…In contrast to MUC1, MUC2 acts as a protective protein and is associated with a more favorable prognosis (26,27). MUC5AC is a gel-forming secreted mucin and serum MUC5AC is likely to be a poor prognostic factor in CC patients (28,29). In the present study, MUC6 expression was a good independent prognostic factor in ICC, which is consistent with previous findings (29,30).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to MUC1, MUC2 acts as a protective protein and is associated with a more favorable prognosis (26,27). MUC5AC is a gel-forming secreted mucin and serum MUC5AC is likely to be a poor prognostic factor in CC patients (28,29). In the present study, MUC6 expression was a good independent prognostic factor in ICC, which is consistent with previous findings (29,30).…”
Section: Discussionsupporting
confidence: 91%
“…However, despite the fact that increased MUC5AC expression correlates with a worse prognosis for patients with lung adenocarcinoma (Yu et al, 1996(Yu et al, , 2005, cholangiocarcinoma (Boonla et al, 2003;Aishima et al, 2006) and PDA (Takikita et al, 2009), a molecular mechanism for MUC5AC in determining the properties of these cancer cells has not been fully elucidated. In this study, we showed that GLI1-upregulated MUC5AC facilitates the migration and invasion of PDA cells through the attenuation of E-cadherin-mediated intercellular adhesion.…”
Section: Gli1-induced Muc5ac Attenuates E-cadherinmentioning
confidence: 99%
“…Serum levels of MUC5AC, another mucin frequently expressed in intrahepatic cholangiocarcinomas, have also been reported to correlate with tumor burden and poor patient survival. 74 In contrast, MUC2, an intestinal-type mucin that is selectively expressed predominantly in well-differentiated and noninvasive mucinous-type intraductal cholangiocarcinomas with gastrointestinal differentiation, 75 predicts a more favorable prognosis. 44,71 MUC2 expression in intraductal papillary neoplasms of the liver was recently demonstrated to be closely related to aberrant expression of the caudalrelated homeodomain intestine-specific transcription factor CDX2.…”
Section: Sirica Hepatology January 2005mentioning
confidence: 99%